Croatian conditionals and epistemic stance - Stanojević, Mateusz-Milan (2011)
Croatian conditionals and epistemic stance In Croatian, ako ‘if’, and kad(a) ‘when’ appear with actual and hypothetical conditionals, da ‘if’ appears with counterfactuals (Silić and Pranjković 2005:348-349). Thus, ako + the present tense in (1) signals an actual conditional, ako + the past tense in (2) signals a hypothetical conditional, and da + the present tense in (3) a counterfactual conditional. (1) Ako nas ujutro nitko ne poveze, otići ćemo vlakom. ‘Unless someone gives us a lift in the morning, we will take the train.’ (2) Ako ih je zaista poslao u Carigrad, bit će tu nešto drugo u igri. ‘If he really sent them to Constantinople, something else must be at play.’ (3) Da danas mogu ponovno birati, ne bih se nikada stranački angažirao. ‘If I could do it all over again today, I would never go into politics’. The data looks parallel to English, where access and epistemic stance signaled by the tense used in the protasis yield different types of conditionals (Cutrer 1994:256-323). However, there are additional facts to be taken into account in Croatian. For instance, the protasis allows a range of verbal forms in actual conditionals: perfective verbs in the present tense (1), the so-called second future (Ako budu ovako igrali, onda će izgubiti ‘If they play like this, they will lose), and the future tense (Ako će ovako igrati, onda će izgubiti ‘If they play like this, they will lose’), whose meanings appear very similar. Similarly, the passive does not adhere to the prescribed tense formation: what is formally a present tense passive (je napisana lit. ‘is written’) may refer to a counterfactual situation requiring the past tense (je bila napisana lit. ‘was written’): (4) Da je ta priča (…) napisana ‘realističkije’, ona zacijelo ne bi mogla biti objavljena 1978. ‘If that story had been written more realistically, it could not have been published in 1978.’ All this (and some other facts) suggests that epistemic stance in Croatian conditionals is based on the interplay of mood, tense, aspect, voice and conjunction, and that the conditional construction is not fully grammaticalized. Based on corpus data (Croatian National Corpus) we list the most frequent patterns (e.g. ako + the perfective present in the protasis, future tense in the apodosis ; da + the past tense in the protasis, the conditional in the apodosis, etc.). We explain their workings in terms of cognitive grammar (e.g. in (1) the epistemic immediacy of the present tense and the perfective verb signal removal from the actual to the epistemically immediate virtual plain ; in (4) the terminal prominence of the n-participle signals removal from the conceptualizer’s viewpoint and may refer to epistemic distance, etc.), listing some of the idiosyncrasies in the cross-Slavic perspective (e.g. the use of kad in conditionals ; the use of the second future, etc.). On a more general scale, these coincide with aspectual data showing that Croatian is a transitional zone among Slavic languages (Dickey 2000). Cutrer, Michelle. 1994. Time and Tense in Narratives and Everyday Language. Ph. D. dissertation, San Diego: University of California, San Diego. Dickey, Stephen M. 2000. Parameters of Slavic Aspect: A Cognitive Approach. Stanford: Center for the Study of Language and Information. Silić, Josip, and Ivo Pranjković. 2005. Gramatika hrvatskoga jezika za gimnazije i visoka učilišta. Zagreb: Školska knjiga.